How Universities Promote Economic Growth - Yusuf, Shahid; Nabeshima, Kaoru (Washington, DC : World Bank, 2012)
This study was initiated in 1999 with the objective of identifying the most promising path to development in light of emerging global and regional changes. The purpose of this volume is to examine the role of universities in enhancing technological capability in Asian as well as other industrial countries. This volume also discusses the University-Industry Links (UIL) policies of national governments, corporations and sub national governments. Case studies, policies, strategies and conclusions for Switzerland, United Kingdom, Netherlands, Japan, Thailand, United States, China, Singapore, and India are all individually examined. The volume also covers topics such as knowledge transmission, knowledge production, knowledge sharing, research and development, lessons learned, best practices and innovation initiatives and their roles for economic growth in relation to UIL.